Proceedings of the First ASEAN Business, Environment, and Technology Symposium (ABEATS 2019) 2020
DOI: 10.2991/aebmr.k.200514.011
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Business Intelligence Adoption on Organizational Performance Among Higher Education Institutions in Malaysia

Abstract: Business Intelligence (BI) ideally provides organizations that embrace them with immerse impact. Very few researches have empirically assessed these claims. There are limited studies of its impacts on organizational performance in the context of higher education institutions (HEIs) in developing countries. The study aims to develop a conceptual framework for the impacts of BI adoption on organizational performance among higher education institutions. A conceptual framework was developed using the Kaplan and No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Business Intelligence Adoption (BIA) is critical to sustaining the success of an organization's strategic objectives, provision of higher quality information, and reengineering of business processes. The impact of BIA ultimately increases the conditions for decision making, which makes BIA a common information technology (IT) innovation (Nazri, Ashaari, Iskandar, & Bakri, 2020). BIA is a term that characterizes many applications of informatics with an affordable basis, used in organizations to examine information so that it turns it into data that will form the basis for choices made by managers (Airinei & Berta, 2012).…”
Section: Business Intelligence Adoption (Bia)mentioning
confidence: 99%
“…Business Intelligence Adoption (BIA) is critical to sustaining the success of an organization's strategic objectives, provision of higher quality information, and reengineering of business processes. The impact of BIA ultimately increases the conditions for decision making, which makes BIA a common information technology (IT) innovation (Nazri, Ashaari, Iskandar, & Bakri, 2020). BIA is a term that characterizes many applications of informatics with an affordable basis, used in organizations to examine information so that it turns it into data that will form the basis for choices made by managers (Airinei & Berta, 2012).…”
Section: Business Intelligence Adoption (Bia)mentioning
confidence: 99%
“…Thus, it's been pointed out by researchers that success is achieved by organizations after the adoption of BI. Therefore, organizations opt to improve as well as upgrade their BI systems on regular basis (Nazri, Ashaari, Iskandar, & Bakri, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The impact of ICT on HEIs' business results has been investigated extensively in the last twenty years, especially because it enables social interaction through various channels [30,31], especially in COVID-19 pandemic conditions. However, it depends on many factors, including the business environment, innovation culture, knowledge and team engineering [30,32,33].…”
Section: Introductionmentioning
confidence: 99%
“…For the aggregation of the sub-variables, it is possible to use different approaches (weighted assessment, statistical techniques and fuzzy approaches). Regarding ICT support, the level of investment at the ICT level of the ICT strategy, the level of management quality, and the process quality level have significant impacts [33]. In this research, the authors observed ICT support in a broader sense than ICT equipment and support by people, similar to Tirto et al [66], in which the term "ICT support" was used to present digital scientific infrastructure according to the priorities of Industry 4.0 and Education 4.0 concepts.…”
mentioning
confidence: 99%
See 1 more Smart Citation